The stream-dwelling larva of the Ruwenzori River Frog, Amietia ruwenzorica, its buccal cavity and pathology of chytridiomycosis - Viertel, Bruno; Veith, Michael; Schick, Susanne; Channing, Alan; Kigoolo, Stephen; Baeza-Urrea, Oscar; Sinsch, Ulrich; Lötters, Stefan (Zootaxa, 2012)
Tadpoles of Amietia ruwenzorica (Pyxicephalidae, Cacosterninae) were collected in the Ruwenzori Mountains, Uganda(identified by DNA barcoding). The ventrally directed enlarged oral disc with a high number of labial tooth rows (LTRF9(4)/9(1)) and the narrow tail with robust caudal musculature characterise them as stream-dwellers. We name this mor-photype the 'common or standard type of stream-adaptation', because special additional adhesive organs are missing in A.ruwenzorica. The uniserially arranged oral teeth of the spoon-shaped type with 16 to 18 cusps per tooth are known fromother anuran larvae, especially from pyxicephalids. The buccal morphology resembles generalized tadpoles with some re-strictions and all features of a suspension-feeding pyxicephalid larva are present in A. ruwenzorica. This leads us to theconclusion that tadpoles of this species are suspension-feeders scraping periphyton off the surface and ingesting bottomand deposit particles. Histopathological and scanning electron microscopy investigations demonstrated the presence of theamphibian chytrid fungus (Batrachochytrium dendrobatidis) in part of our material resulting in signs of chytridiomycosis indicated by the loss of labial teeth and by corrosion of jaw sheaths.